2017
DOI: 10.3390/soc7030018
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Factors Influencing the Design of Intergenerational Digital Games: A Systematic Literature Review

Abstract: The main purpose of this paper is to review the benefits and factors to be taken into consideration for the design of intergenerational digital games. We conducted a systematic in Scopus, Web of Science, PsicInfo, Pubmed and Science Direct, finally including 16 empirical studies written in English. The identified benefits were found to fall into four main categories, i.e., (1) reinforcing family bond, (2) enhancing reciprocal learning (3) increasing understanding of the other generation and (4) reducing social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 32 publications
1
39
0
3
Order By: Relevance
“…Generally speaking game playing experiences vary based on the respective game genre(s) been played (De Schutter & Brown, 2015;Marston, 2013a;Marston et al, 2016;Nacke & Lindley, 2008;Nacke & Lindley, 2009;Voida & Greenberg, 2012;Whitelock et al, 2014). For example, players may experience deep meaningful game experiences through role-playing games, whereas simulation or puzzle games may not elicit the same experience (Connell & Dunlap, 2020). It is also important to understand the role of player motivations on game experience.…”
Section: Amendments From Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking game playing experiences vary based on the respective game genre(s) been played (De Schutter & Brown, 2015;Marston, 2013a;Marston et al, 2016;Nacke & Lindley, 2008;Nacke & Lindley, 2009;Voida & Greenberg, 2012;Whitelock et al, 2014). For example, players may experience deep meaningful game experiences through role-playing games, whereas simulation or puzzle games may not elicit the same experience (Connell & Dunlap, 2020). It is also important to understand the role of player motivations on game experience.…”
Section: Amendments From Versionmentioning
confidence: 99%
“…The fact that games are playful, fun, interactive spaces differentiates them from other forms of mediated communication, such as text messaging or social media (Kowert, 2015). They allow individuals to connect through play, which is an important facet of psychological well-being throughout the lifespan (Connell & Dunlap, 2020). Play in and of itself is associated with reduced stress and depression, as well as a releasing of endorphins (Robinson et al, 2019).…”
Section: Gaming In a Time Of Covid-19mentioning
confidence: 99%
“…In 2017, a systematic review conducted by De la Hera et al (2017) identified 16 papers fitting the in/exclusion criteria and via data analysis identified four categories associated to the benefits of intergenerational gaming; (1) reinforcing family bond, (2) enhancing reciprocal learning, (3) increasing understanding of the other generation and finally reducing social anxiety. De la Hera et al (2017) noted factors that informed and should be considered when considering the influences of designing videogames for intergenerational game play; (1) player-centric, motivations, resulting in wanting to play different games and the variance of abilities. Although, the second factor was game-centric, and included additional facets such as goal-oriented play and space-related forms of interactions.…”
Section: Intergenerational Gamingmentioning
confidence: 99%
“…The proportion of older adults worldwide is growing (United Nations 2017). Although digital games have become a popular pastime activity among older adults (Interactive Software Federation of Europe 2018), there is a limited number of studies on older adults and children as intergenerational digital game co-designers (de la Hera et al 2017;Loos et al 2019).…”
Section: Resultsmentioning
confidence: 99%